The Macroeconomics of Scaling-up Aid : the Cases of Benin, Niger, and Togo. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
In September 2007, the UN Secretary General launched the Millennium Development Goals (MDG) Africa Steering and Working Groups. The Steering Group brings together the leaders of multilateral institutions to identify practical steps needed for Africa to achieve the MDGs. The Managing Director of the IMF is a member of the Steering Group. The Working Group supports the Steering Group and is comprised of thematic groups in education, agriculture, health, infrastructure and trade facilitation, statistics, aid predictability, and MDG operationalization at the country level. The following three notes assess the macroeconomic implications of the spending of scaled-up aid to Benin, Niger, and Togo in line with that promised by the G-8 at Gleneagles, Scotland in 2005.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet